277 Translating for equity impact: A community-engaged approach to integrate health equity into the Translational Science Benefits Model - Mia LaBrier; Stephanie Andersen; Julie Heidbreder; Laura Brossart; Todd Combs; Douglas Luke; Shannon Casey (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The Translational Science Benefits Model (TSBM) offers an approach for evaluating research impact on public health and society. Since its development in 2017, there has been an increased focus on science’s impacts on equity. This poster describes efforts to integrate equity into the TSBM. METHODS/STUDY POPULATION: Adaptation of the TSBM includes 3 phases: 1) literature scan of equity impacts, 2) community engagement listening sessions, and 3) model refinement. First, we conducted a scan of the clinical and translational sciences literature for articles that measured equity impacts associated with the TSBM. From the articles, we extracted both equity considerations related to existing TSBM benefits and potential equity-focused benefits. Next, we will present the dimensions of new and existing benefits to several community member panels engaged in research and evaluation. We will use their input to prioritize and refine adaptations to the model (phase 3). RESULTS/ANTICIPATED RESULTS: Our literature scan identified equity dimensions of the original 30 TSBM benefits and 15 potential benefits for inclusion in the model, including community partnerships, community capacity building, workforce development, and social determinants of health, among others. To ensure that community priorities also inform identification of equity impacts of clinical and translational research, we will review and refine the model through a series of community engagement sessions planned for Fall 2023. The sessions will inform final adaptations, which will result in an expanded approach evaluating the impact of scientific activities to include impacts on health equity. DISCUSSION/SIGNIFICANCE: The TSBM provides a framework for clinical and translational scientists to plan for, track, and demonstrate the broader impacts of their work. Including equity impacts can help increase consideration of equity in science and help to more clearly make the link between research and equity impact.